A new species in the leafhopper genus Processina (Hemiptera: Cicadellidae: Mileewinae: Mileewini) from China - Yu, Tinghao; Zhang, Yalin (Zootaxa, 2022)
A new species in the Mileewinae genus Processina Yang, Deitz & Li, 2005, P. hunanensis sp. nov., from China is described. A checklist and a key to all known species of Processina are provided.